The reported prevalence of aircrew fatigue and the contributing factors within the South African aviation industry - Blair, Dylan Ross (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Fatigue in aviation results from the complex interaction of various factors (both work and non-work-related) that are important to understand when attempting to manage it. Managing fatigue effectively is important given that it has and continues to influence crew wellness and aviation safety. One of the ways of managing fatigue is through appropriately designed Flight Time Limitations (FTLs) however; in South Africa there have been calls from the unions and the crew to update these in line with the latest science and operational demands and insights. Doing this requires the generation of context specific data, which this thesis aimed to provide as an initial step. Firstly, this study aimed to explore the reported prevalence of fatigue across the South African aviation industry. Secondly, it elucidated what factors (both work and non-work related) crew perceived contributed to fatigue and lastly, the crew"Ÿs perceptions regarding the current FTLs were explored. Methods: To realize the aims of the study, an online survey was developed using existing literature initially, and through consulting with and getting information from aviation industry stakeholders and other experts in the field of aviation and fatigue. This consultation (which occurred over a number of iterations of the survey) ensured that there was a balance between the scientific and the actual operational perspectives on how best to explore crew perceptions around fatigue. The finalized survey was divided into five parts: part one was consent to participate; part two included questions pertaining to the participants"Ÿ demographic information; part three included questions pertaining to the crews"Ÿ perceptions around fatigue (its prevalence, its impact on safety and how it affected crew); part four explored crew"Ÿs perceptions on fatigue contributory factors, both work and non-work related; finally part five included questions pertaining to crew perceptions about the current South African FTLs, specifically their concerns, suggestions for improvement and any aspects they considered as fatigue mitigating. The survey was made available via the South African Civil Aviation Authority"Ÿs (SACAA) website as well as via the industry stakeholder"Ÿs networks that encouraged all crew across the different sectors of the industry to participate. All numerical data collected were analysed descriptively through inferential statistics, while the qualitative data were analysed using thematic analysis. Results: 194 participants completed the survey, 167 were from cockpit and 27 were from the cabin crew. The results of the study highlight that there is a high perceived prevalence of fatigue. The crew also recognized that fatigue is a significant safety risk, but less indicated that fatigue interfered with their ability to do their duties. Crew reported that the length of duties, number of sectors flown, insufficient sleep at night, early sign-on"Ÿs, late sign-offs, working too many consecutive days in a row, inadequate or irregular sleep before and during periods of duty, night flying, bad weather, severe turbulence, having young children or dependents to look after, financial stress, extended commuting to get to and from work, and poor diet were some of the work and non-work-related contributory factors to fatigue. In line with these findings, questions around the perceived concerns about the current FTLs revealed that crew were concerned about unclear definitions of the civil aviation regulations (CARs), the lack of control of disruptive rostering schedules, periods of high workload due to the number of sectors flown per duty, the length of duty periods and effects of being on standby duty, inadequate rest between duties and strings of duty. The crew also had concerns regarding the Flight Duty Periods (FDPs) where the crew were concerned with the flying limits being used as targets by the operators, a lack of science applied to the FDPs, and that the current FDPs are outdated. The recommendations included limiting disruptive rostering schedules by altering standby provisions for the crew, instilling a block roster schedule, disallowing double signing on and off on the same day, and reducing split shifts. The crew also recommended adjusting duty durations by adjusting daily and monthly limits, tapering duty lengths, but also limiting discretionary extensions. Increasing rest provision was another recommendation suggested by the crew and included increasing the number of rest days off as well as the minimum hours of rest between duties needs to be increased. The fatigue mitigating aspects were minimal if any. Conclusion: Overall the study revealed that there is a high perceived prevalence of fatigue within this sample of the South African aviation industry and that the concerns outlined by crew around the contributory factors to fatigue are consistent with previous research, but also reflect the unique operating context of South Africa. This study serves as a base from which to explore more specific areas of the crew working time that are disruptive to sleep. This may help operator"Ÿs roster duties in a more predictable way to limit the incidence of fatigue, while also offering the opportunity for the regulator and other stakeholders to focus their efforts on how to better design the current FTLs to limit the prevalence and risks associated with crew fatigue.
Keywords: Fatigue; Flight crews; Fatigue in the workplace; Sleep deprivation; Sleep-wake cycle; Air travel Safety measures; Airlines -- South Africa